Membangun Generasi Qur'ani: Kegiatan Penyuluhan BTQ di Desa Sumberejo - Hijazzi, Akhmad Faruq; Khakim, Muhammad Zahir Luthfil; Mufila, Safana Fitriani; Lathifah, Kurnia; Hanafi, Muhammad Sofyan; Septiani, Sheilla; Toha, Ahmad Muzaki; Karim, Abdul (Islamic Extension Guidance Study Program (BPI) of the Faculty of Da'wah and Communication, 2024)
Abstract: Qur'anic literacy education (BTQ) has become very important in building a Qur'anic generation in Muslim societies. This research focuses on BTQ extension activities in Sumberejo Village, which aim to improve the ability to read and write the Qur'an among adult mothers. Through a qualitative approach, which included observations and interviews, the study found that this extension program not only improved participants' technical skills, but also deepened their understanding of the teachings of the Qur'an and its application in daily life. The results showed that after attending the counseling, participants experienced significant improvements in their confidence and ability to recite the Qur'an, which had a positive impact on their children's religious education. Therefore, BTQ counseling in Sumberejo Village can be categorized as a strategic effort to empower the community and shape the character of a better Qur'anic generation.Abstrak: Pendidikan Baca Tulis Al-Qur'an (BTQ) menjadi sangat penting dalam membangun generasi Qur'ani di masyarakat Muslim. Penelitian ini berfokus pada kegiatan penyuluhan BTQ di Desa Sumberejo, yang bertujuan untuk meningkatkan kemampuan membaca dan menulis Al-Qur'an di kalangan ibu-ibu dewasa. Melalui pendekatan kualitatif, yang meliputi observasi dan wawancara, penelitian ini menemukan bahwa program penyuluhan ini tidak hanya meningkatkan keterampilan teknis peserta, tetapi juga memperdalam pemahaman mereka tentang ajaran Al-Qur'an serta penerapannya dalam kehidupan sehari-hari. Hasil penelitian menunjukkan bahwa setelah mengikuti penyuluhan, peserta mengalami peningkatan signifikan dalam kepercayaan diri dan kemampuan membaca Al-Qur'an, yang berdampak positif pada pendidikan agama anak-anak mereka. Oleh karena itu, penyuluhan BTQ di Desa Sumberejo dapat dikategorikan sebagai upaya strategis untuk memberdayakan komunitas dan membentuk karakter generasi Qur'ani yang lebih baik.